Partisipasi Perempuan dalam Meningkatkan Usaha Pengolahan Pisang di Desa Teniga Kabupaten Lombok Utara - nurul istiqomah nurul istiqomah (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2024)
Women's participation in the world of entrepreneurship, both large and small scale, can influence economic growth in a positive direction. Women's participation in the world of work has made a major contribution to family welfare, especially in the economic sector with high poverty rates and the difficulty of obtaining a material standard of living, including clothing. , food and shelter, then requires involvement in improving the family economy, including requiring the role of a woman in increasing household income. This research took place in Teniga Village, Tanjung District, North Lombok Regency. Teniga village is one of the villages that produces quite a lot of bananas in NTB, therefore the people of Teniga village take advantage of the plantation sector to create employment opportunities to increase the banana processing business in Teniga Village. The aim of this research is to explore the extent of women's participation in the banana processing business in Teniga Village, North Lombok Regency and what factors influence the level of women's participation. In order to see the active role or participation of women in managing and advancing Micro, Small and Medium Enterprises (MSMEs). This study uses a qualitative method. To collect data, researchers conducted direct observation, interviews and documentation. From the results of the research carried out, there are several factors, especially in the development of this banana processing business, such as the absence of follow-up from the village government to develop this business, which is a matter of resources, funds and readiness of the business owner. Micro, Small and Medium Enterprises "Banana Flowers "This has been going on for about four years since Indonesia was affected by Covid 19 and after Lombok was hit by an earthquake, this business has been very advanced and has customers in various corners with income that can reach IDR 500,000 - IDR 1,000,000 per day, even Micro, Small and Medium Enterprises (MSMEs). These banana flowers have reached overseas for export. Therefore, the existence of Micro, Small and Medium Enterprises (MSMEs) can open up employment opportunities, especially for housewives in improving the "Banana Flower" Micro, Small and Medium Enterprises.